Environmental Stressors Interplay with Top-Down and Bottom-Up Effects Upon Shell Structure and Function of an Intertidal Marine Snail - Garcia-Herrera, C (Elsevier Ltd, 2026)
Mollusc gastropods have evolved complex shells to protect their soft tissues from biotic and abiotic stress, but the impact of biological and environmental interactions on shell properties is not well understood. This study assessed how the individual and combined effects of increased temperature and p CO2 affect the structural and functional properties in shells of the intertidal snail Tegula atra , considering predator risk from the crab Homalaspis plana and changes in the nutritional quality of its food source, the brown kelp Lessonia spicata . Ocean acidification (OA) and ocean warming (OW) significantly affected growth rate and calcification of snails, with greater impacts under predator risk (top-down) than food quality (bottom-up) influences. FTIR-ATR analyses of the organic composition of shell periostracum indicated that OA conditions increased total organic matter, while polysaccharides, and carbonate content signals showed complex interactive effects under OA and OW conditions, with minor predator cue effects, while the nutritional value of the food source alters polysaccharides and lipids signals. Functional properties (resistance) of the shell material were affected by OA, OW, and predator cues but not by food quality source. These findings provides a novel understanding of how interacting climate stressors and trophic dynamics shape the structural (biomineralization) and functional (biomechanical) resilience of intertidal gastropods. © © 2025. Published by Elsevier Ltd.